Retrospective observational study of the choice of anaesthesia for caesarean section in patients with eclampsia - Jordaan, Meandra (Department of Anaesthesia and Perioperative Medicine, 2021)
Background Anaesthesia for ceasarean section (CS) in women with eclampsia is a major clinical challenge, and there are limited data concerning the rationale for the choice of technique, and the short-term outcomes. A retrospective audit was performed on practice at a tertiary referral centre in Cape Town. Methods The primary outcome of the audit was the proportion of patients with eclampsia receiving either spinal anaesthesia (SA) or general anaesthesia (GA) for CS, and the assessment of the rationale for the choice of method. A convenience sample of the records of one hundred consecutive patients with eclampsia admitted to the Maternity Centre at Groote Schuur Hospital from 2009- 2013, were studied. Patient demographics, clinical details and outcomes (including relevant results of special investigations), were recorded. The number and percentage of patients receiving GA or SA were documented. The presence or absence of factors influencing selection of the method of anaesthesia, including Glasgow Coma Scale (GCS), degree of urgency of CS, trauma to the oropharynx, number of seizures, control of blood pressure, and the availability of and/or platelet count prior to anaesthesia, were noted. In addition, complications of anaesthesia were described, and short-term maternal and neonatal outcomes were recorded. Results One hundred patient records were screened, and there were 11 exclusions; therefore 89 patient records were analysed. Seven/89 (7.9%) received SA and 82/89 (92.1%) GA. One patient required conversion to GA because of the occurrence of a seizure during attempted SA. All patients receiving spinal anaesthesia were stable and had no postoperative complications. Overall, 63 (70.8%) had a preoperative GCS< 14, and 26 (29.2%) patients had GCS ≥14. Seven patients in the subgroup with GCS ≥14 had SA, and the remaining 19 received GA. GA was performed because there was no platelet count available in 3, pulmonary oedema in 2, difficult airway due to a bitten tongue during a seizure in 2, fetal bradycardia in 2, HELLP syndrome in 1, renal failure in 1, and patient refusal in 1 patient. In 7 women, there was no clear reason why GA was chosen. The median [IQR] Apgar scores at 1 minute were lower in patients receiving GA [(5) (1-9) and 4 (1-9)] in patients with GCS ≥14 and < 14 respectively, versus 8 (6-9) for SA. The number (%) of neonates with Apgar scores ≥ 7 at 1 minute in patients who had SA, was 6 (85.7), compared with 3 (13.6) and 12 (17.9) in patients having GA with GCS ≥14 and < 14 respectively. There were 2 stillbirths and 2 neonatal deaths in the GA group. The median [IQR] length of stay in patients with GCS ≥ 14 was 1 day in the group receiving SA and 2 days in those who had GA; patients with GCS< 14 were ventilated for 3 days. No patients receiving SA required postoperative ventilation, whereas 5/19 (26.3%) patients with GCS ≥14 who received GA required ventilation, for 2 days. Seven patients with GCS< 14 had cerebral oedema, and 2 had cerebral infarcts. There were 2 maternal deaths. Conclusions In this audit, a small percentage of women with eclampsia received SA for CS. A review of the case records suggests that more patients could have safely received SA. A larger prospective audit is required to establish factors influencing safety of spinal anaesthesia for CS in women with eclampsia.